2020
DOI: 10.3390/ijerph18010083
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Medical Records of Trauma Patients Admitted to the Emergency Unit of a University Hospital, Upper Egypt

Abstract: Trauma records in Egyptian hospitals are widely suspected to be inadequate for developing a practical and useful trauma registry, which is critical for informing both primary and secondary prevention. We reviewed archived paper records of trauma patients admitted to the Beni-Suef University Hospital in Upper Egypt for completeness in four domains: demographic data including contact information, administrative data tracking patients from admission to discharge, clinical data including vital signs and Glasgow Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… 57–94 The second group included 15 publications, which were cited above as containing ‘AFEM-CC quality indicators exact match’ data, but which contained additional ‘AFEM-CC quality indicators near match’ data. 22 25 26 28 29 31 33 34 39 41 45 46 54–56 This brings the total number of publications containing ‘AFEM-CC quality indicators near match’ data to 53 and the total number of data points identified within those publications to 87. Tables 2 and 3 contain summary ‘AFEM-CC quality indicators near match’ data, while further detail about each included publication is provided in online supplemental appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 57–94 The second group included 15 publications, which were cited above as containing ‘AFEM-CC quality indicators exact match’ data, but which contained additional ‘AFEM-CC quality indicators near match’ data. 22 25 26 28 29 31 33 34 39 41 45 46 54–56 This brings the total number of publications containing ‘AFEM-CC quality indicators near match’ data to 53 and the total number of data points identified within those publications to 87. Tables 2 and 3 contain summary ‘AFEM-CC quality indicators near match’ data, while further detail about each included publication is provided in online supplemental appendix 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 39 studies were seen to contain ‘AFEM-CC quality indicators exact match’ data for process clinical and/or outcome quality indicators 18–56. Only 8% (3 of 39) of these studies explicitly mentioned quality in the stated research objectives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical documentation, even in patients with cardiac arrest 33 and especially with children 34 , 35 has long been recognised as an issue. This problem is more significant in low resource settings, 36 , 37 which also bear the largest burden of drowning globally. 1…”
Section: Discussionmentioning
confidence: 99%
“…in a study reviewing 539 medical records for trauma patients at Beni-Suef university. 37 The study clearly showed significant defects in 4 studied criteria, including demographic data, administrative fields, clinical description of injury, and the casualty event, which was concluded to be inadequate for developing trauma registry data.…”
Section: Deficits Of Trauma Care In Egyptmentioning
confidence: 95%